Deletion of mstna and mstnb impairs the immune system and affects growth performance in zebrafish. Issue 72 (January 2018) - Wang, Chao; Chen, Yan-Ling; Bian, Wan-Ping; Xie, Shao-Lin; Qi, Ge-Le; Liu, Li; Strauss, Phyllis R.; Zou, Ji-Xing; Pei, De-Sheng
Abstract: Myostatin (Mstn) is a negative regulator of muscle development in vertebrates. Although its function in muscle growth has been well studied in mammals and fish, it remains unclear whether or how mstn functions in the immune system. In this study, mstna −/- and mstnb −/- homozygous zebrafish were firstly generated using CRISPR/Cas9 (Clustered regularly interspaced short palindromic repeats/CRISPR associated protein 9). Deletion of mstnb but not mstna enhanced growth performance. Although survival rates under normal conditions were slightly decreased in both strains, mortality after dexamethasone-induced stress was increased by ∼30%. Furthermore, transcriptional levels of several critical immune-related genes were decreased, and the ability to withstand exposure to pathogenic E. tarda was decreased, compared with that of controls. In mstnb −/- but not mstna −/- zebrafish, expression of NF-κB subunits and several pro-inflammatory cytokines failed to respond to E. tarda exposure except nfkb1, c-rel and tnfα . Taken together, these results indicate that mstnb but not mstna plays a key role in zebrafish muscle growth. While each paralogue contributes to the response to bacterial insult, mstnb affects the immune system through activation of the NF-κB pathway, and mstna is likely to act upstream of NF-κB at some as yet unidentified target. Highlights: The mstna −/- and mstnb −/- zebrafish were generated using the CRISPR/Cas9 strategy. The mstnb −/- zebrafish showed the increases of body lengths and weights. Deletion of mstna and mstnb all impaired their immune system. Deletion of mstnb might affect the NF-κB pathway.